2018
DOI: 10.1111/1365-2435.13092
|View full text |Cite
|
Sign up to set email alerts
|

Primary productivity explains size variation across the Pallid bat's western geographic range

Abstract: Body size is associated with many aspects of the life history, ecology and physiology of animals. Within a species, body size can vary substantially across space and time, and the mechanisms generating these patterns have been the focus of evolutionary and ecology research. Bergmann’s rule predicts a negative relationship between body size and temperature across the geographic range of endothermic animals; larger animals have a lower surface to volume ratio, which would allow for greater heat conservation. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 92 publications
(190 reference statements)
1
22
0
1
Order By: Relevance
“…In contrast, the predictions of James's rule have been thoroughly supported at the intraspecific level in mammals (Kubo & Takatsuki, ; Meiri, ; Pincheira‐Donoso, ; Rodríguez & Hawkins, ) and birds (Ashton, ). In bats, some studies have indicated that larger body sizes were found in cooler environments, consistent with the predictions of Bergmann's rule/James's rule (Bogdanowicz, ; Burnett, ; Dietz et al, ; Kelly et al, ; Storz et al, ). However, several studies have shown the inverse of James's rule in the greater horseshoe bat, and have suggested that resource rules (relating to resource abundance, availability, and size) may be used to explain this pattern (Budinski et al, ; Kryštufek, ; Wu et al, ).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In contrast, the predictions of James's rule have been thoroughly supported at the intraspecific level in mammals (Kubo & Takatsuki, ; Meiri, ; Pincheira‐Donoso, ; Rodríguez & Hawkins, ) and birds (Ashton, ). In bats, some studies have indicated that larger body sizes were found in cooler environments, consistent with the predictions of Bergmann's rule/James's rule (Bogdanowicz, ; Burnett, ; Dietz et al, ; Kelly et al, ; Storz et al, ). However, several studies have shown the inverse of James's rule in the greater horseshoe bat, and have suggested that resource rules (relating to resource abundance, availability, and size) may be used to explain this pattern (Budinski et al, ; Kryštufek, ; Wu et al, ).…”
Section: Discussionsupporting
confidence: 60%
“…In contrast, the predictions of James's rule have been thoroughly supported at the intraspecific level in mammals (Kubo & Takatsuki, 2015;Meiri, 2011;Pincheira-Donoso, 2010;Rodríguez & Hawkins, 2010) and birds (Ashton, 2002). In bats, some studies have indicated that larger body sizes were found in cooler environments, consistent with the predictions of Bergmann's rule/James's rule (Bogdanowicz, 1990;Burnett, 1983;Dietz et al, 2006;Kelly et al, 2018;Storz et al, 2001).…”
Section: Patterns and Causes Of Bm Variationmentioning
confidence: 93%
See 1 more Smart Citation
“…Endemism is one of the main factors predicting the risk of extinction in bats, that is associated with habitat specialist species (Welch & Beaulieu, 2018). Besides landscape composition and structure, other factors such as primary productivity may influence bat traits related to vagility and food intake (Kelly, Friedman, & Santana, 2018). Thus, bat responses to environmental degradation are probably not linear, and its predictability may depend on a methodological framework that incorporates the multidi-…”
Section: Functional Traits and The Scale Of Effectmentioning
confidence: 99%
“…For example, while heat production implies high metabolic expenditure of energy for endotherms, the dependence of ectotherms on environmental heat neutralises such pressures (Brown et al 2004, Angilletta 2009); finally 3) the 'seasonality (or 'fastingendurance') rule', predicts that increasing seasonality selects for increased body size to enhance tolerance to unstable environments (Lindsey 1966, Boyce 1979, Calder 1984. Given the contrasting mechanisms that these hypotheses offer to explain the same phenomenon, evidence supporting them has been conflicting across lineages (Meiri et al 2005, Yom-Tov and Geffen 2006, Olalla-Tarraga and Rodriguez 2007, Olalla-Tarraga et al 2009, Oufiero et al 2011, Pincheira-Donoso and Meiri 2013, Gouveia and Correia 2016, Kelly et al 2018, Amado et al 2019). Furthermore, our understanding of body size macroecology has fundamentally been advanced based on above-ground organisms, while analyses on fossorial lineages remain anecdotal (Meiri and Dayan 2003, Measey and Van Dongen 2006, Feldman and Meiri 2014.…”
Section: Introductionmentioning
confidence: 99%